The Korean economy : perspectives for the twenty-first century - Yi, Hyŏng-gu, 1940- (Albany : State University of New York Press, 1996)
"In The Korean Economy, Hyung-Koo Lee, formerly South Korea's Minister of Labor, chronicles South Korea's economic development from 1945-1994 and the public policies that have shaped that development. In the past, the South Korean government supported protectionist policies. Mr. Lee, arguing that these policies no longer serve the long-term interest of South Korea's economy, supports the allowance of greater private-sector initiatives, a fundamental paradigm shift in South Korea's economic policy. He argues that if South Korea is to become a major economic power, the government should withdraw from the economic front line. He also provides a succinct analysis of the vast economic potential of a reunified Korea and discusses the pros and cons of two alternative scenarios for the South Korean economy."--Jacket.
Includes bibliographical references (pages 239-246) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Korea (South) -- Economic conditions; Korea (South) -- Economic policy; Corée du Sud -- Conditions économiques.; Corée du Sud -- Politique économique.; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Economics -- Comparative; BUSINESS & ECONOMICS -- Economic Conditions; BUSINESS & ECONOMICS -- Economic History; Economic history; Economic policy; Korea (South); Economische politiek; Zuid-Korea.; Business & Economics; Economic History